Evaluation of bokashi fermentation leachate as a biofertilizer in urban horticulture : inorganic plant nutrient content in bokashi leachate and its effect as a fertilizer on pak choi - Lind, Olle (SLU/Dept. of Plant Breeding (from 130101), 2014)
The leachate obtained from bokashi fermentation household vessels, are among proponents of the bokashi method believed to be useful as a biofertilizer. The bokashi fermentation method does not lead to foul odours as it is anaerobically fermented in air-tight bins with lactic acid bacteria, among other groups of microorganisms, and is therefore interesting in the light of an increasing interest of urban farming and unexploited resources of plant mineral nutrients within the urban area.